Enterprise Restructuring Evaluation - Bivainis, Juozas; Tamošiūnas, Andrius (Ekonomika, 2004)
The paper analyses the evaluation model of enterprise restructuring programmes, specifying the techniques of its application in the context of the following proposed criteria: the market share; financial capacity; business development potential; product competitiveness; productivity. The benefit of application of this model in restructuring enterprises is revealed. The greater possibilities to rationalize the restructuring process as well as the use of human, material and financial potentials, to develop potentials of an enterprise and thus to increase its competitiveness are shown.